DA DEPENDÊNCIA DA ÁGUA ÀS ROTAS DE NÉCTAR E FOLHAS COLORIDAS: SEQUÊNCIA DE ENSINO INVESTIGATIVA PARA O ESTUDO DO PROCESSO DE REPRODUÇÃO DAS PLANTAS - Silva, Magda Medeiros Schu (2023)
This work was developed within the scope of the Professional Master's program in Science and Mathematics Education at Franciscan University (UFN), in the research line of Teaching and Learning in Science and Mathematics. Through an investigative teaching sequence, the aim was to contribute to the improvement of teaching about plant reproduction in the context of high school. The development of skills and specific content is related to the theme of plant reproduction. The Natural Sciences area, in its classes and approaches, is one of the appropriate scenarios for the development of skills and competencies necessary for the comprehensive education of students through the perspective of the Inquiry-Based Teaching Approach. This study specifically addresses Competency 3, which involves investigating problem situations and evaluating applications of scientific and technological knowledge and their implications in the world, using procedures and languages specific to the Natural Sciences, to propose solutions that consider local, regional, and/or global demands, and communicate their discoveries and conclusions to various audiences in different contexts and through various media and digital information and communication technologies of the Natural Sciences, as foreseen in the National Common Curricular Base (BNCC) and the mobilization of its concepts. The proposed investigative sequence is expected to last for six class periods. The analysis and evaluation of the educational product, an E-book containing the investigative teaching sequence on Sexual Reproduction of Terrestrial Plants, were carried out with ten Biology teachers selected from a convenience sample. Content analysis was used for data analysis. The analysis categories were: a) The potential of applying an Investigative Teaching Sequence in the study of plant reproduction, and b) The challenges of implementing an Investigative Teaching Sequence on plant reproduction in the Common Formation Itineraries of the New High School. As obtained results, we can highlight that the educational product, according to the interviewees, constitutes an important teaching material for the teacher, facilitating the approach to the theme, which sometimes the teacher may not be very familiar with. We found that the educational product, presenting the investigative methodology, expands spaces for dialogue, group work, enabling greater interaction with the topic studied, as well as promoting curiosity and a disposition for investigation. Thus, problematizing and discussing the sexual reproductive adaptations that have placed plant species at an advantage to resist selective pressures enable the knowledge of these adaptations and the dissemination of scientific knowledge. Experiencing and expanding this repertoire contextualizes teaching and inspires investigative pedagogical practices that position the student as the protagonist of their meaningful learning process.